Respuesta :
A solution is extraneous when the denominator of the function becomes zero when the solution is substituted.
Equating each of the options to 0:
x^2 +3x-4 = 0
x = 1 and -4
You can check the other options but they won't result to having a solution of x=-4
Therefore, the possible denominator of the function is x^2 +3x-4
Equating each of the options to 0:
x^2 +3x-4 = 0
x = 1 and -4
You can check the other options but they won't result to having a solution of x=-4
Therefore, the possible denominator of the function is x^2 +3x-4
Answer:
Option 1
Step-by-step explanation:
We will find the solution for the expression in option 1
[tex]x^2+3x-4[/tex]
[tex]x^2+4x-x+4[/tex]
[tex]x^2-x+4x-4[/tex]
[tex]x(x-1)+4(x-1)[/tex]
[tex](x+4)(x-1)[/tex]
Hence, x=1 and x=-4 willl be the solution
Hence, [tex]x^2+3x-4[/tex] will be in denominator.
Hence, Option 1 is correct
Option 2,3 and 4 are discarded.